Budaya Patriarki dalam Tradisi Sasak Lombok (Analisis Wacana Kritis dalam Kumpulan Cerpen Jangan Pulang Jika Kamu Perempuan Karya Riyana Rizki) - Fatihrahma, Mahyuni; Hilmiyatun, Hilmiyatun; Amrullah, Roni (LPPM Institut Pendidikan Nusantara Global, 2025)
This study examines the patriarchal culture present in Riyana Rizki's collection of short stories, Jangan Pulang Jika Kamu Perempuan, through Sara Mills' approach. The purpose of this study is to find out the patriarchal culture that occurs in the merariq tradition in the tradition of the Lombok Sasak community. This study uses a descriptive qualitative method with a data blunt technique based on the results of readers' understanding of the collection of short stories and conducting interviews with the author and several readers. Data analysis was carried out by classifying data from short story excerpts based on the theme raised, and then analyzed using Sara Mills' theory, namely the position of subject-objects and the position of the reader. The results of the study show that the merariq tradition in the Sasak Lombok community, which is depicted in the short story